Clinical Obesity Services in Public Hospitals in Australia: a position statement based on expert consensus. Issue 3 (23rd April 2018) - Atlantis, E.; Kormas, N.; Samaras, K.; Fahey, P.; Sumithran, P.; Glastras, S.; Wittert, G.; Fusco, K.; Bishay, R.; Markovic, T.; Ding, L.; Williams, K.; et al.
Summary: We aimed to describe the current state of specialist obesity services for adults with clinically severe obesity in public hospitals in Australia, and to analyse the gap in resources based on expert consensus. We conducted two surveys to collect information about current and required specialist obesity services and resources using open‐ended questionnaires. Organizational level data were sought from clinician expert representatives of specialist obesity services across Australia in 2017. Fifteen of 16 representatives of current services in New South Wales ( n = 8), Queensland ( n = 1), Victoria ( n = 2), South Australia ( n = 3), and the Australian Capital Territory ( n = 1) provided data. The composition of services varied substantially between hospitals, and patient access to services and effective treatments were limited by strict entry criteria (e.g. body mass index 40 kg/m 2 or higher with specific complication/s), prolonged wait times, geographical location (major cities only) and out‐of‐pocket costs. Of these services, 47% had a multidisciplinary team (MDT), 53% had an exercise physiologist/physiotherapist, 53% had a bariatric surgeon and 33% had pharmacotherapy resources. Key gaps included staffing components of the MDT (psychologist, exercise physiologist/physiotherapist) and access to publicly funded weight loss pharmacotherapy and bariatric surgery. There was consensus on the need for significant improvements in staff, physical infrastructure, access to services, education/training in obesity medicine and targeted research funding. Based on the small number of existing, often under‐resourced specialist obesity services that are located only in a few major cities, the vast majority of Australians with clinically severe obesity cannot access the specialist evidence based treatments needed.